I’m the last person you’d work with’. Funeral Professionals’ Place in Death Rites - Christidis, Yiannis; Kouros, Theodoros (My University, 2021)
This video essay negotiates aspects of the notion of death, with regards to the way death professionals, workers and even mourners deal with it in their everyday lives. Visually, selected video shots from their practices guide the viewer to delve into theoretical notions and ethnographic data, showcasing both research and conceptual characteristics. Sonically, the video essay is identified through experimental sound design, which utilizes granular synthesis and death-related soundscape recordings, mostly obtained from processed field recordings from related spaces, such as a cemetery, a mortuary, a church, etc. The narration scheme is enforced by pieces of written text, deriving primarily from anthropological and sociological theories of death, as well as from related interviews excerpts, their respective research quotes, and minimal discourse-provoking phrases, which appear sparsely and strategically on screen.
Keywords: video essay